OPTIMALISASI PRODUKSI TANAMAN JAGUNG (ZEA MAYS) MELALUI APLIKASI BIOCHAR DARI LIMBAH TONGKOL JAGUNG - Hadianti, Iga Zanuar; Sule, Suryaman; Harwanto, Harwanto (Agriculture Faculty of Flores University, 2025)
Maize (Zea mays) is one of the most important staple crops, alongside rice. However, its production has been continuously declining in recent years. The primary cause of this decline is the deteriorating soil condition, including increasingly acidic soil pH and very low levels of organic carbon and organic matter. This study aims to determine the effective application dosage of biochar derived from corncob waste to improve soil fertility and maize production. The experiment was conducted using a Completely Randomized Design (CRD) in polybags. There were five treatments with five replications: Control (P1), corncob biochar 32 g/polybag (P2), corncob biochar 64 g/polybag (P3), corncob biochar 128 g/polybag (P4), and corncob biochar 256 g/polybag (P5). The parameters observed included soil pH, organic carbon, organic matter, plant height, cob length, and number of dry kernels. The results showed significant differences among treatments, with the best performance found in treatment (P4), corncob biochar 256g/polybag. There was a noticeable improvement before and after the application, with soil pH increasing from 4.25 to 6.75, organic carbon from 1.4% to 3.6%, and organic matter from 2.42% to 6.15%. For plant growth parameters, the best results were also achieved at the biochar application 256g/polibag (P4). Therefore, the higher the amount of corncob biochar applied, the more effective it is in enhancing the growth and production of maize.